Factors Associated With Adherence To Immunosuppressive Therapy And Barriers In Asian Kidney Transplant Recipients - Ganjali R; Ghorban Sabbagh M; Nazemiyan F; Mamdouhi F; Badiee Aval S; Taherzadeh Z; Heshmati Nabavi F; Golmakani R; Tohidinezhad F; Eslami S (ImmunoTargets and Therapy, 2019)
Raheleh Ganjali,1 Mahin Ghorban Sabbagh,2,3 Fatemeh Nazemiyan,2,4 Fereshteh Mamdouhi,2,3 Shapour Badiee Aval,5 Zhila Taherzadeh,6 Fatemeh Heshmati Nabavi,7 Reza Golmakani,8 Fariba Tohidinezhad,1 Saeid Eslami1,9,10 1Department of Medical Informatics, Faculty of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 2Kidney Transplantation Complications Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 3Department of Nephrology, Montaseriyeh Organ Transplantation Hospital, Mashhad University of Medical Sciences, Mashhad, Iran; 4Department of Nephrology, Ghaem Hospital, Mashhad University of Medical Sciences, Mashhad, Iran; 5Complementary Medicine Research Center, Faculty of Traditional Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 6Neurogenic Inflammation Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 7School of Nursing and Midwifery, Mashhad University of Medical Sciences, Mashhad, Iran; 8Department of Emergency Medicine, Doctor Shariati Hospital, Mashhad University of Medical Sciences, Mashhad, Iran; 9Pharmaceutical Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 10Department of Medical Informatics, University of Amsterdam, Amsterdam, The NetherlandsCorrespondence: Saeid EslamiDepartment of Medical Informatics, Mashhad University of Medical Sciences, Azadi Street, Mashhad, IranTel +98 513 800 2429Fax +98 513 800 2445Email Eslamis@mums.ac.irBackground: Medication non-adherence is the major risk factor for rejection episodes. The aim of this study was to determine the risk factors associated with adherence to immunosuppressive regimen and its barriers among kidney transplant (KT) recipients.Methods: A cross-sectional study was performed in two outpatient post-transplant clinics in Mashhad, northeast of Iran. All patients who attended the clinics from August to October 2017 were included. Patients’s knowledge, adherence to immunosuppressive regimen, and quality of life were measured using the Kidney Transplant Understanding Tool, Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS), and SF-12V2 questionnaire, respectively. The barriers in adhering immunosuppressive regimen were investigated by Immunosuppressive Therapy Barriers Scale. Logistic regression was used to screen the significant risk factors of medication non-adherence.Results: In this study, 244 KT recipients were included with a mean age of 39.6±12.5 years. Based on the BAASIS score, 111 (45.5%) patients were adherent to immunosuppressive regimen. Female patients were more likely to be adherent (OR=0.48, p<0.01). The patients with higher level of quality of life were more likely to follow immunosuppressive medications (OR=1.078, p<0.05). The main barriers were as follows: concurrent use of many immunosuppressants, lack of knowledge about the usefulness of immunosuppressive medications, confusion in medication taking, and difficulty in remembering medication taking.Conclusion: More than half of the KT recipients were non-adherence to immunosuppressive regimen. These findings highlight the need for designing interventions in order to reduce or eliminate these barriers and consequently increase medication adherence among KT recipients.Keywords: immunosuppressive regimen, medication adherence, quality of life, kidney transplantation